Inhaled nitric oxide improves transpulmonary blood flow and clinical outcomes after prolonged cardiac arrest: a large animal study - Derwall, Matthias; Ebeling, Andreas; Nolte, Kay Wilhelm; Weis, Joachim; Rossaint, Rolf; Ichinose, Fumito; Nix, Christoph; Fries, Michael; Brücken, Anne (Critical care (London, England), 2015)
The probability to achieve a return of spontaneous circulation (ROSC) after cardiac arrest can be improved by optimizing circulation during cardiopulomonary resuscitation using a percutaneous left ventricular assist device (iCPR). Inhaled nitric oxide may facilitate transpulmonary blood flow during iCPR and may therefore improve organ perfusion and outcome. Ventricular fibrillation was electrically induced in 20 anesthetized male pigs. Animals were left untreated for 10 minutes before iCPR was attempted. Subjects received either 20 ppm of inhaled nitric oxide (iNO, n = 10) or 0 ppm iNO (Control, n = 10), simultaneously started with iCPR until 5 hours following ROSC. Animals were weaned from the respirator and followed up for five days using overall performance categories (OPC) and a spatial memory task. On day six, all animals were anesthetized again, and brains were harvested for neurohistopathologic evaluation. All animals in both groups achieved ROSC. Administration of iNO markedly increased iCPR flow during CPR (iNO: 1.81 ± 0.30 vs 1.64 ± 0.51 L/min, p < 0.001), leading to significantly higher coronary perfusion pressure (CPP) during the 6 minutes of CPR (25 ± 13 vs 16 ± 6 mmHg, p = 0.002). iNO-treated animals showed significantly lower S-100 serum levels thirty minutes post ROSC (0.26 ± 0.09 vs 0.38 ± 0.15 ng/mL, p = 0.048), as well as lower blood glucose levels 120-360 minutes following ROSC. Lower S-100 serum levels were reflected by superior clinical outcome of iNO-treated animals as estimated with OPC (3 ± 2 vs. 5 ± 1, p = 0.036 on days 3 to 5). Three out of ten iNO-treated, but none of the CONTROL animals were able to successfully participate in the spatial memory task. Neurohistopathological examination of vulnerable cerebral structures revealed a trend towards less cerebral lesions in neocortex, archicortex, and striatum in iNO-treated animals compared to CONTROLs. In pigs resuscitated with mechanically-assisted CPR from prolonged cardiac arrest, the administration of 20 ppm iNO during and following iCPR improved transpulmonary blood flow, leading to improved clinical neurological outcomes.